OmpA, a Common Virulence Factor, Is Under RNA Thermometer Control in Yersinia pseudotuberculosis - Scheller, Daniel; Twittenhoff, Christian; Becker, Franziska; Holler, Marcel; Narberhaus, Franz (Frontiers in Microbiology, 2021)
The outer membrane protein OmpA is a virulence factor in many mammalian pathogens. In previous global RNA structure probing studies, we found evidence for a temperature-modulated RNA structure in the 5'-untranslated region (5'-UTR) of the Yersinia pseudotuberculosis ompA transcript suggesting that opening of the structure at host-body temperature might relieve translational repression. Here, we support this hypothesis by quantitative reverse transcription PCR, translational reporter gene fusions, enzymatic RNA structure probing, and toeprinting assays. While ompA transcript levels decreased at 37°C compared to 25°C, translation of the transcript increased with increasing temperature. Biochemical experiments show that this is due to melting of the RNA structure, which permits ribosome binding to the 5'-UTR. A point mutation that locks the RNA structure in a closed conformation prevents translation by impairing ribosome access. Our findings add another common virulence factor to the growing list of pathogen-associated genes that are under RNA thermometer control.